Advantages and Disadvantages of the Different Types of Working Hours’ Organisation - Titopoulou, Maria; Ganeva, Ralitsa; Staykova, Jeni; Titopoulos, Efstathios (European Journal of Economics and Business Studies, 2019)
The variety of existing work schedules offers advantages and disadvantages for workers, as well as for their employers. While some flexibility in working hours is oriented to the needs of workers (beyond the minimum standards required for the protection of the employed), another is focused on meeting the needs of businesses (in the literature concerning the working hours, it is often called “variation”).